Fates and Travel Times of Denmark Strait Overflow Water in the Irminger Basin* - Koszalka, Inga Monika; Haine, Thomas W. N.; Magaldi, Marcello G. (Journal of Physical Oceanography, 2013)
The Denmark Strait Overflow (DSO) supplies about one-third of the North Atlantic Deep Water and is critical to global thermohaline circulation. Knowledge of the pathways of DSO through the Irminger Basin and its transformation there is still incomplete, however. The authors deploy over 10 000 Lagrangian particles at the Denmark Strait in a high-resolution ocean model to study these issues. First, the particle trajectories show that the mean position and potential density of dense waters cascading over the Denmark Strait sill evolve consistently with hydrographic observations. These sill particles transit the Irminger Basin to the Spill Jet section (65.25°N) in 5–7 days and to the Angmagssalik section (63.5°N) in 2–3 weeks. Second, the dense water pathways on the continental shelf are consistent with observations and particles released on the shelf in the strait constitute a significant fraction of the dense water particles recorded at the Angmagssalik section within 60 days (~25%). Some particles circulate on the shelf for several weeks before they spill off the shelf break and join the overflow from the sill. Third, there are two places where the water density following particle trajectories decreases rapidly due to intense mixing: to the southwest of the sill and southwest of the Kangerdlugssuaq Trough on the continental slope. After transformation in these places, the overflow particles exhibit a wide range of densities.